2012
DOI: 10.1002/pd.4009
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges of atrioventricular valve areas by means of four‐dimensional ultrasonography using spatiotemporal image correlation in the rendering mode

Abstract: Reference curves for fetal atrioventricular valve areas were determined and presented good reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…According to Fleiss [31], an ICC of 0.81-1.00 ensures an almost perfect reliability that may be adopted in clinical practice. In this respect, Rolo et al [15] obtained an ICC of ≥0.93 for intra- and interobserver reproducibility of the measurement of the fetal tricuspid valve surface area using cardio-STIC application in the rendering mode, whereas Nardozza et al [17] obtained an ICC of 0.99 for interobserver reproducibility of the measurement of the interventricular septum surface area using 3DUS in the rendering mode.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Fleiss [31], an ICC of 0.81-1.00 ensures an almost perfect reliability that may be adopted in clinical practice. In this respect, Rolo et al [15] obtained an ICC of ≥0.93 for intra- and interobserver reproducibility of the measurement of the fetal tricuspid valve surface area using cardio-STIC application in the rendering mode, whereas Nardozza et al [17] obtained an ICC of 0.99 for interobserver reproducibility of the measurement of the interventricular septum surface area using 3DUS in the rendering mode.…”
Section: Discussionmentioning
confidence: 99%
“…The upper limit of 33 weeks 6 days of gestation was established because after this GA, the fetus position on the back and the imaging artifacts from the ribs are more frequent, hampering or even preventing the adequate analysis of fetal cardio-STIC [13,14,15,16,17]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, STIC and VOCAL can be used to calculate cardiac volume, and Uittenbogaard et al (2010aUittenbogaard et al ( , 2010b, Herberg et al (2011) and Hamill et al (2011) reported that imaging of fetal cardiac structures and volumetry, using STIC and VOCAL, is a reliable and accurate method for calculating volumes of 30 mL upward, both in vivo and in vitro. Although caution should be exerted in the calculation of cardiac structures in both the pediatric and adult settings, Rolo et al (2013) have reported the mean area of the tricuspid and mitral valves to range from 0.19 to 0.20 cm 2 at 18 wk and from 0.93 to 1.06 cm 2 at 33 wk of gestation, respectively. In addition, the calculated reference range for the fetal interventricular septum has been found to correlate with gestational age (r 5 0.81) and to increase from 0.47 cm 2 at 18 wk to 2.42 cm 2 at 33 wk of gestation, respectively ).…”
Section: -Dus and Fetal Echocardiogrammentioning
confidence: 97%
“…Thus, to obtain relevant information about cardiac function is possible due to the CHD [11]. More recently, a new approach to STIC rendering mode analysis obtained measurements of mitral and tricuspid valves areas, and also and the interventricular septum, determining reference values for these parameters, making it feasible to apply in suspected or pathological cases [12,13].…”
Section: Fig 2 -Use Of Tui With Simultaneous Visualization Of Sequenmentioning
confidence: 99%